BIRMAN-SCHWINGER PRINCIPLE FOR TWO-PARTICLE DISCRETE SCHRÖDINGER OPERATORS ON LATTICES - Abdusaitov, Doston Shirinboy o‘g‘li (Educational Research in Universal Sciences, 2023)
We consider a system of two identical bosons moving on the hypercubic lattice , and interacting through attractive short range potentials µV (µ > 0) and the two-particle Schrödinger operators (k)- , k associated to the system, where is the d - dimensional torus. We study the Birman-Schwinger principle for two-particle Schrödinger operators.